Chicago plant aims to reduce energy costs using GE's ZeeLung MABR. Issue 10 (October 2015) - Unknown
Abstract : As part of its plan to become energy neutral by 2023, the Metropolitan Water Reclamation District of Greater Chicago (MWRD) is evaluating GE's new ZeeLung Membrane Aerated Biofilm Reactor (MABR) technology.